Amorphous silica biomineralizations in Polytrichum strictum Menzies ex Brid. (Bryophyta) - Benvenuto, María Laura (2013)
In this study, the presence of amorphous silica biomineralizations (silicophytoliths) in individuals of Polytrichum strictum collected from Tierra del Fuego, Argentina was analysed. Gametophyte and sporophyte samples were subjected to calcination and staining techniques, through which the biomineralizations obtained were observed and described by optical and scanning electron microscopes. Lastly, their composition was analysed by energy dispersive spectroscopy. In both gametophyte and sporophyte silica skeletons comprising thin elongated silicophytoliths with blunt, round or acute ends were observed. These morphologies may correspond to the silicification of the costa or midrib region of the leaves (in the gametophyte) and the seta (in the sporophyte) and to the silicification of the awns of the leaves. The other morphologies found were silica skeletons comprising silicified walls of tabular polygonal cells, probably derived from the silicification of the cells of the unistratose lamina of leaves. Energy dispersive spectroscopy analyses and the use of a phenol-staining technique confirmed the silicon composition of these biomineralizations. The results obtained comprise the first description of amorphous silica biomineralization in mosses and the implications of the silicification process in this taxon are discussed. The data obtained will be relevant not only for anatomical, but also for palaeobotanical studies, since the preservation of these structures in the soil after the decomposition of organic matter, might allow the identification of mosses in the fossil record.